Computational challenges in the simulation of nonlinear electroelasticity - Steinmann, Paul; Vu, Duc Khoi (Computer Assisted Methods in Engineering and Science, 2017)
Nonlinear electroelasticity is not a new problem, its theory involving nonlinear deformation and nonlinear material behavior has been well established. However, the numerical simulation of nonlinear electroelasticity is until now still far from satisfactory, especially when the interaction between electric fields and matter cannot be considered as confined in the finite space occupied by the matter. It is understood that under the application of an electric field, the deformation of an elastic body is governed not always by what happens inside the material body but in many cases also by the environment surrounding it. This is notably true in the case of electronic electroactive polymers, the materials that emerge today as a leading candidate in developing artificial muscles. In this work, we present a numerical analysis of nonlinear electroelasticity by assuming large deformation, nonlinear polarization and by paying attention to the contribution of the free space surrounding the bodies of interest.